Anti-Bladder-Tumor Effect of Baicalein from Scutellaria baicalensis Georgi and Its Application In Vivo. (17th March 2013) - Wu, Jin-Yi; Tsai, Kun-Wei; Li, Yi-Zhen; Chang, Yi-Sheng; Lai, Yi-Chien; Laio, Yu-Han; Wu, Jiann-Der; Liu, Yi-Wen
Abstract : Some phytochemicals with the characteristics of cytotoxicity and/or antimetastasis have generated intense interest among the anticancer studies. In this study, a natural flavonoid baicalein was evaluated in bladder cancer in vitro and in vivo . Baicalein inhibits 5637 cell proliferation. It arrests cells in G1 phase at 100 μ M and in S phase below 75 μ M. The protein expression of cyclin B1 and cyclin D1 is reduced by baicalein. Baicalein-induced p-ERK plays a minor role in cyclin B1 reduction. Baicalein-inhibited p65NF- κ B results in reduction of cell growth. Baicalein-induced pGSK(ser9) has a little effect in increasing cyclin B1/D1 expression instead. The translation inhibitor cycloheximide blocks baicalein-reduced cyclin B1, suggesting that the reduction is caused by protein synthesis inhibition. On the other hand, neither cycloheximide nor proteasome inhibitor MG132 completely blocks baicalein-reduced cyclin D1, suggesting that baicalein reduces cyclin D1 through protein synthesis inhibition and proteasomal degradation activation. In addition, baicalein also inhibits cell invasion by inhibiting MMP-2 and MMP-9 mRNA expression and activity. In mouse orthotopic bladder tumor model, baicalein slightly reduces tumor size but with some hepatic toxicity. In summary, these results demonstrate the anti-bladder-tumor properties of the natural compound baicalein which shows a slight anti-bladder-tumor effect in vivo .